Use of the socio-ecological model to explore factors that influence the implementation of a diabetes structured education programme (EXTEND project) inLilongwe, Malawi and Maputo, Mozambique: a qualitative study - C. Bamuya; J. C. Correia; E. M. Brady; D. Beran; D. Harrington; A. Damasceno; A. M. Crampin; Ana Magaia; Naomi Levitt; M. J. Davies; M. Hadjiconstantinou (BMC, 2021)
Abstract Background Diabetes Self-Management Education and Support (DSMES) programmes are vital for type 2 diabetes mellitus (T2DM) management. However, they are limited in Sub-Saharan Africa (SSA). To address this gap, a DSMES, namedEXTEND was developed in Lilongwe (Malawi) and Maputo (Mozambique). This qualitative study aimed to explore factors that influence the implementation of DSMES in these settings. Methods The Socio-ecological model was applied to explore factors influencing the implementation of DSMES in SSA. Data was analysed using the Framework method and constant comparative techniques. Sixty-six people participated in the study: people with T2DM who participated in the EXTEND programme; healthcare professionals (HCPs), EXTEND educators, EXTEND trainers, and stakeholders. Results Our findings indicate that there is a need to develop an integrated and dedicated diabetes services in SSA healthcare systems, incorporating culturally adapted DSMES and tailored diabetes training to all professions involved in diabetes management. Traditional media and the involvement of community leaders were proposed as important elements to help engage and promote DSMES programmes in local communities. During the design and implementation of DSMES, it is important to consider individual and societal barriers to self-care. Conclusion Findings from this study suggest that multi-faceted factors play a significant role to the implementation of DSMES programmes in LICs. In the future, EXTEND could be incorporated in the development of diabetes training and dedicated diabetes services in SSA healthcare systems, acting as an educational tool for both people with T2DM and HCPs. This project was supported by the Medical Research Council GCRF NCDs Foundation Awards 2016 Development Pathway Funding.